결절맥락막혈관병증에서 유리체강내 애플리버셉트 주입술의 단기 효과 - 양 헌(Heon Yang); 전혜민(Hye Min Jeon); 김상원(Sang Won Kim); 윤희성(Hee Seong Yoon); 최우석(Woo Seok Choae) (Daihan angwa haghoi jabji, 2015)
목적: 이전에 치료한 적 없는 결절맥락막혈관병증(polypoidal choroidal vasculopathy, PCV) 환자에 유리체강내 aflibercept (EyleaⓇ; Regeneron Pharmaceuticals Inc., Tarrytown, NY, USA and Bayer, Basel, Switzerland)를 주입한 후 단기간 시력 및 망막의 해부학적 구조에 미치는 변화를 확인하고자 하였다. 대상과 방법: 2014년 5월부터 9월 사이에 본원에서 PCV로 진단 받고 aflibercept 주입술을 받은 환자 중 과거 치료 받은 적 없었던16명 16안에 대해 의무기록을 후향적으로 분석하였다. Aflibercept 주입술 전과 후 1, 2, 3개월째 최대교정시력 및 빛간섭단층촬영(optical coherence tomography, OCT) 상 소견과 3개월째 인도시아닌그린혈관조영술(indocyanine green angiography, ICGA) 상변화를 관찰하였다. 결과: 최대교정시력(logarithm of the minimum angle of resolution, logMAR)은 치료 전 0.75 ± 0.60에서 치료 후 1, 2, 3개월에 0.74 ± 0.64, 0.71 ± 0.63, 0.57 ± 0.53으로 점차 호전되는 양상을 보였고, 3개월째에 유의한 시력 상승을 보였다(p＜0.05). OCT 상중심와두께는 치료 전 379 ± 130 μm에서 치료 후 281 ± 92, 247 ± 54, 232 ± 51 μm로 유의하게 감소되었다(p＜0.05). OCT 상 망막색소상피박리 완전 관해율은 치료 후 43, 55, 50%, 망막하액은 67, 83, 92%, 망막내액은 33, 60, 60%였다. ICGA상 결절은치료 후 3개월에 86%에서 감소되었다. 결론: PCV에서 aflibercept 주입술은 단기간 형태학적 개선을 유도하는 효과적이고 안전한 방법으로 보인다. 최대교정시력은 해부학적 지표들의 호전소견에 비하여 술 후 2개월까지 의의 있는 차이가 보이지 않았으나, 3개월째에는 유의한 상승을 보였다. Purpose: To evaluate the short-term effect of intravitreal aflibercept (Eylea®; Regeneron Pharmaceuticals Inc., Tarrytown, NY, USA and Bayer, Basel, Switzerland) on the visual outcomes and retinal anatomic changes of patients with polypoidal choroidal vasculopathy (PCV). Methods: Intravitreal Eylea® was injected into 16 eyes of 16 patients with PCV in this retrospective case study. After therapy, the patients were followed up for over 3 months. Changes in best-corrected visual acuity (BCVA) and central foveal thickness (CFT) using optical coherence tomography (OCT) and abnormal vasculature on indocyanine green angiography (ICGA) were evaluated. Results: The mean log MAR BCVA was 0.75 ± 0.60 at baseline, 0.74 ± 0.60 and 0.71 ± 0.63 at 1 and 2 months, respectively (p > 0.05) and 0.57 ± 0.53 at 3 months (p < 0.05) after treatment. The mean CFT was 379 ± 130 μm at baseline, 281 ± 92 μm, 247 ± 54 μm, and 231 ± 51 μm at 1, 2, and 3 months, respectively, after treatment (p < 0.05). Complete resolution was 43%, 55%, and 50% at 1, 2, and 3 months, respectively in pigment epithelial detachment (PED), 67%, 83%, and 92% at 1, 2, and 3 months, respectively in subretinal fluid (SRF) and 33%, 60%, and 60% at 1, 2, and 3 months, respectively in intraretinal fluid (IRF) using OCT. The polypoidal lesions in ICGA decreased in 12 of 14 eyes (86%). Conclusions: Intravitreal injection of Eylea® with PCV reduced CFT due to decreased retinal PED, SRF, IRF and occluded effectively the polypoidal lesion leaking. Compared with baseline, mean BCVA at the 3-month follow-up was significantly improved. KCI Citation Count: 2